The impact of social media and other Information and Communications Technology (ICTs) on the evolution of civil unrest as a political risk factor: The case of Turkey - Louw, Eunet (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.